2015
DOI: 10.5599/admet.3.3.173
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Blood Brain Barrier Permeability in Traumatic Brain Injury Research

Abstract: The blood brain barrier plays an important role in traumatic brain injury, serving at the crossroads of secondary injury and potential therapies. In regards to trauma, this barrier contains an array of cellular and molecular components that protect the central nervous system from derangements in water homeostasis and inflammation. Preclinical and clinical assays have been developed to describe and quantify blood brain barrier permeability in relation to the integrity of these blood brain barrier components and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Due to the increased chance of detection in controls, it is less precise than paracellular tracer permeability, like dextran and inulin 54 . However, in a study by Liao et al 55 , EB and dextran were compared and indicated that EB could detect BBB permeability, but non-specific signals were reduced in shams using dextrans. So, the increase in extravasation in injured animals in these experiments was likely due to BBB permeability caused by the TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the increased chance of detection in controls, it is less precise than paracellular tracer permeability, like dextran and inulin 54 . However, in a study by Liao et al 55 , EB and dextran were compared and indicated that EB could detect BBB permeability, but non-specific signals were reduced in shams using dextrans. So, the increase in extravasation in injured animals in these experiments was likely due to BBB permeability caused by the TBI.…”
Section: Discussionmentioning
confidence: 99%
“…computerized tomography (CT), magnetic resonance imaging (MRI), positive emission tomography) by potentially allowing continuous, repeatable bedside-monitoring as well economical, safety, logistical and radiation exposure benefits. 710 Despite these advantages, studies on TBI patients using contrast-enhanced NIRS have been limited and the utility of this technique in brain trauma care is still subject to investigation. This review aims to analyze the methods adopted so far to assess cerebral blood flow ( italicCBF) and blood–brain barrier (BBB) integrity using contrast-enhanced NIRS with ICG on animals and humans; the limits of these assessments in TBI patients; the solutions proposed to overcome them; and to discuss how the use of contrast-enhanced NIRS could address some of the current clinical challenges in the care of TBI patients.…”
Section: Introductionmentioning
confidence: 99%